Autonomy in the Dock: Oscar Wilde’s First Trial - Bénédicte Coste (Cahiers Victoriens et Edouardiens)
The 1895 Wilde trials are usually seen as either the trial of non-normative sexualities or as enabling a definition of the homosexual in Great Britain at the close of the nineteenth century. However I wish to discuss Wilde’s own words during his trial against the Marquess of Queensberry and envisage them as part of a Wildean discourse advocating personal radical autonomy, which had already appeared in ‘The Soul of Man under Socialism’ (1891). Such a discourse can be seen as Wilde’s political statement about Aestheticism that sustained all his acts including taking the Marquess to court. The individual politics of autonomy that Wilde advocated can also be discussed in relation to the idea of autonomy as elaborated by the 20th–century philosopher C. Castoriadis.